Some factors influencing oviposition in an artificial host by the pupal parasitoid Brachymeria intermedia (Nees) (Bollettino di zoologia agraria e bachicoltura, 2024)
Attempts to identify factors capable of inducing Brachymeria intermediato oviposit in an artificial host are reported. The development of an artificialsubstrate for in vitro egg laying of this hymenopterous parasitoid is alsodescribed. When presented with a choice between pupae of the factitious hostGalleria mellonella and a blank cell in a Y tube olfactometer the females did notshow a significant olfactory preference for the pupae. The response of B. intermediafemales to G. mellonella pupae washed in hexane or untreated was alsonot significantly different. The role of kairomonal cues in the cuticle of G. mellonellapupae in attracting B. intermedia females was therefore not clear. Cylindricalhost shape, on the other hand, was apparently important in inducing parasitoidoviposition. In fact, the females were observed to probe cylinder-shapedartificial substrates with their ovipositors even in the absence of chemical cue.When cylinder-shaped and purposefully flattened G. mellonella cuticles wereexposed to parasitoid females oviposition holes were recorded only in the formerand none in the latter. Cylinder-shaped artificial hosts composed of an agar-watersuspension and G. mellonella haemolymph encapsulated in Parafilm were henceprepared and exposed to B. intermedia females. Some eggs were recorded in artificialpupae containing 50% or 25% haemolymph. No eggs were found in 'thepupae containing agar-water suspension alone, or 75% or 100% haemolymph.These results suggest that G. mellonella haemolymph contains ovipositional kairomones,an excess of which, however, prevents B. intermedia females from ovipositing.
Keywords: pupal parasitoids; oviposition; artificial host; Brachymeria intermedia